APPLICATION OF LASER SCANNING DATA IN SOLVING TERRITORIAL PLANNING PROBLEMS - Horb, O.; Kasianov, V.; Nesterenko, S.; Nelin, Ye. (Municipal economy of cities. Series: «Economy science», 2024)
The article aims to thoroughly investigate and analyse the possibilities of using laser scanning data in spatial planning. The main goal is to identify the potential of this technology to improve the efficiency and accuracy of planning processes, particularly in the urban environment. The LiDAR (Light Detection and Ranging) data integration into territorial planning is fundamental to modern urban management frameworks. Using the precise and comprehensive geospatial data obtained through LiDAR scanning provides a reliable basis for conducting in-depth analysis and strategic decision-making in territorial development initiatives. LiDAR technology offers unparalleled accuracy and detail, enabling urban planners to effectively map and visualise various aspects of urban environments, including topography, land use patterns, infrastructure, and natural features. With this extensive information, stakeholders can gain valuable insights into existing spatial dynamics, identify potential areas for development or conservation, and assess the impact of proposed projects on the surrounding landscape. Moreover, integrating LiDAR data facilitates the optimisation of urban resource management processes. City authorities can streamline land use planning, infrastructure development, and environmental management efforts by accurately delineating land plots and infrastructure networks. In turn, it promotes more efficient allocation of resources, minimises operational costs, and enhances overall urban sustainability. Furthermore, LiDAR technology is crucial in enhancing urban resilience and adaptability. Generating high-resolution elevation models and floodplain maps allows urban planners to identify areas prone to natural hazards such as floods, landslides, or coastal erosion. With this knowledge, city planners can implement proactive measures to mitigate risks, improve disaster preparedness, and safeguard community well-being. In contemporary urban challenges, such as climate change and rapid urbanisation, LiDAR technology is becoming increasingly indispensable. By embracing LiDAR technology, urban planners can develop more resilient and sustainable cities better equipped to withstand and adapt to evolving environmental, social, and economic pressures. In essence, the effective utilisation of LiDAR data in territorial planning enhances spatial planning accuracy and fosters innovation, resilience, and sustainability within urban environments. By harnessing the power of LiDAR technology, cities can pave the way toward a more prosperous, equitable, and resilient future for generations to come.